Nilai diagnostik thoraks foto pada pasien coronavirus disease-2019 (covid-19) terhadap hasil real time polymerase chain reaction (RT-PCR) di Rumah Sakit Umum Daerah Wangaya Denpasar periode Juni-November 2021 - Anak Agung Parama Swari Khrisna; Ni Luh Jaya Kirana (Intisari Sains Medis, 2022)
Introduction: COVID-19 is an infectious disease caused by a new virus causes that attacks the upper respiratory tract and the lungs. The numbers of cases and deaths have increased on a daily basis on the scale of a global pandemic. Chest X-ray images have proven useful for monitoring various lung diseases and have recently been used to monitor the COVID-19 disease. Imaging modalities such as chest x-rays have the benefit of providing initial imaging before confirming with RT-PCR examination. The purpose of this study was to determine the value of the diagnostic examination of the chest x-ray compared to the RT-PCR examination which is the gold standard in diagnosing COVID-19.Methods: This study used a diagnostic study design with a retrospective approach at Wangaya Hospital, Denpasar during the period June-November 2021. Analysis of the diagnostic test used cross tabulation and then calculated sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (LR+), negative likelihood ratio (LR-), and accuracy were performed.Results: Thorax imaging diagnostic test value compared with the gold standard RT-PCR examination in form of sensitivity, specificity, PPV, NPV, LR+, LR-, and accuracy was 78%, 23%, 84%, 16.6%, 1.01, 0.95, and 69% respectively.Conclusion: Thorax imaging provide a high sensitivity and accuracy of diagnostic in person with clinical presentation of COVID-19. Pendahuluan: COVID-19 merupakan suatu penyakit menular yang disebabkan oleh virus baru dan menyerang saluran pernapasan bagian atas dan paru-paru. Jumlah kasus dan kematian telah meningkat setiap hari dalam skala pandemik global. Modalitas pencitraan seperti thoraks foto memiliki manfaat untuk memberikan pencitraan awal sebelum mengkonfirmasi dengan pemeriksaan RT-PCR. Tujuan penelitian ini adalah untuk mengetahui nilai pemeriksaan diagnostik yang dimiliki thoraks foto dibandingkan dengan pemeriksaan RT-PCR yang merupakan baku emas dalam mendiagnosis COVID-19.Metode: Penelitian ini menggunakan desain studi diagnostik dengan pendekatan retrospektif di Rumah Sakit Umun Daerah Wangaya Denpasar selama periode Juni-November 2021. Analisis uji diagnostik menggunakan tabulasi silang kemudian perhitungan sensitivitas, spesitifitas, positive predictive value (PPV), negative predictive value (NPV) positive likelihood ratio (LR+), negative likelihood ratio (LR-) dan akurasi dilakukan.Hasil: Nilai uji diagnostik thoraks foto dibandingkan dengan pemeriksaan baku emas RT-PCR berupa sensitivas, spesitifitas, PPV, NPV, LR+, LR-, dan akurasi adalah masing-masing 78%, 23%, 84%, 16.6%, 1.01, 0.95, dan 69%.Simpulan: Thoraks foto memberikan sensitivitas dan akurasi diagnostik yang tinggi secara langsung pada presentasi klinis COVID-19.